“The students are getting very restless”: Student Power at the Provincial Normal School, 1869–1879 - Grant, John (Journal of the Royal Nova Scotia Historical Society, 2023)
While “student power” is generally associated with university life during and after the 1960s, it was on full display in 1869 and 1878 at the Provincial Normal School. The PNS in Truro, NS (the precursor of the Nova Scotia Teachers College) was opened in 1855 to prepare teachers for the province’s schools. In 1869, its students opposed the person appointed as its new principal and in 1878 they objected to the instruction offered by at least one of their professors. These are unusual events in the story of higher education in this province. But, as events unfolded, student power was alive and well at PNS in those instances and School and provincial authorities could only ignore it at their peril.